Shear Bond Strength of Self-Adhering Flowable Composite and Resin-modified Glass Ionomer to Two Pulp Capping Materials - Doozandeh, Maryam; Koohpeima, Fatemeh; Firouzmandi, Maryam; Abbassiyan, Forugh (Iranian Endodontic Journal, 2016)
Introduction: The aim of this study was to compare the shear bond strength of a self-adhering flowable composite (SAFC) and resin-modified glass ionomer (RMGI) to mineral trioxide aggregate (MTA) and calcium-enriched mixture (CEM) cement. Methods and Materials: A total of 72 acrylic blocks with a central hole (4 mm in diameter and 2 mm in depth) were prepared. The holes were filled with MTA (sub group A) and CEM cement. The specimens of both restorative materials were divided into 6 groups; overall there were 12 groups. In groups 1 and 4, SAFC was used without bonding while in groups 2 and 5 SAFC was used with bonding agent. In all these groups the material was placed into the plastic mold and light cured. In groups 3 and 6, after surface conditioning with poly acrylic acid and rinsing, RMGI was placed into the mold and photo polymerized. After 24 h, the shear bond strength values were measured and fracture patterns were examined by a stereomicroscope. Data were analyzed using the two-way ANOVA and student’s t-test. Results: The use of bonding agent significantly increased the shear bond strength of FC to MTA and CEM cement (P=0.008 and 0.00, respectively). In both materials, RMGI had the lowest shear bond strength values (2.25 Mpa in MTA and 1.32 Mpa in CEM). The mean shear bond strength were significantly higher in MTA specimen than CEM cement (P=0.003). There was a significant differences between fracture patterns among groups (P=0.001). Most failures were adhesive/mix in MTA specimen but in CEM cement groups the cohesive failures were observed in most of the samples. Conclusion: The bond strength of self-adhering flowable composite resin to MTA and CEM cement was higher than RMGI which was improved after the additional application of adhesive.